Literatura e multiculturalidade no conto de fadas: um estudo de “Chapeuzinho Vermelho” - Pereira, Natanaela de Sousa (2024)
Our aim is to study three different versions of “Little Red Riding Hood” in a comparative perspective, allowing the identification of multicultural aspects present in the works we are researching. This study’s corpus consists of the following Brazilian illustrated works of “Little Red Riding Hood”, all happening in Brazil, in the country’s Northeast and North: A Peleja de Chapeuzinho Vermelho com o Lobo Mau (2011), written by Arievaldo Viana and illustrated by Jô Oliveira; Chapeuzinho de Couro (2013), written and illustrated by Agostinho Ornellas; and Chapeuzinho Vermelho e o Boto-Cor-deRosa (2020), written by Cristina Agostinho and Ronaldo Simões Coelho, and illustrated by Walter Lara. The works are studied regarding linguistic, literary, and imagetic aspects; this helps us identify their multicultural characteristics and leads to the research's enrichment. The following questions direct our corpus reading and analysis: do the works selected continue the version registered by Charles Perrault and the Brothers Grimm, or how do they differ from them when it comes to illustrations and textual composition? To what extent do the works reflect the same contemporary society they integrate? How is it possible to see in the corpus the marks left by multiculturalism in geographical, temporal, and spacial level? The research hypothesis reveals the works selected to be analyzed have features marked by local multicultural influences; brought by their authors and/or illustrators, both in the verbal and visual text. This may influence a partial or total change in the narrative when compared to the classic version – known worldwide and cataloged –, by Charles Perrault and the Brothers Grimm. The main authors to form this study's theoretical foundation are Bruno Bettelheim (2019), Linda Hutcheon (1985), Lígia Cademartori (2010), María Teresa Andruetto (2021), Nelly Novaes Coelho (1987; 2000; 2012), Regina Zilberman (2001), Karin Hueck (2016), Robert Darnton (1986), Cleber Fabiano da Silva (2013), Fabiano Moraes (2022), Jack Zipes (1993), and Sophie Van Der Linder (2018). Regarding this research's final considerations, it became evident there is an appropriation of “Little Red Riding Hood” versions, with the aim of forming national identities. The rewritings of such tale are responses to European stories' translations, as the authors and illustrators of the works studied here intended to put their personal and/or collective point of view on this fairy tale to imprint the regionalist culture of Brazil's North and Northeast in them